Does the choice of stock selection criteria affect the performance of Sharīʿah-compliant equity portfolios? - Muhammad Wajid Raza (ISRA International Journal of Islamic Finance, 2021)
Purpose There are a number of differences in the current Sharīʿah screening guidelines formulated by Sharīʿah scholars associated with world-renowned index providers and financial institutions. The purpose of this study is to highlight the consequences of such differences on the portfolio level outcomes for Sharīʿah-compliant investors. This study also investigates the cost of adopting an alternative stock selection methodology. Design/methodology/approach Seven Sharīʿah-compliant equity portfolios (SCEPs) are created from the active constituents of the S&P 500. Size, sector allocation and financial performance of the resulting seven portfolios are evaluated for the period 1984-2019. Style analysis is performed to attribute the difference in financial performance caused by the choice of selection criteria to different risk factors. The cost of switching the selection criteria is evaluated with turnover analysis and break-even transaction cost. Findings The choice of stock selection criteria has a significant effect on the size, sector bets and financial performance of the portfolios. Those portfolios which are constructed with market capitalization-based screens outperform portfolios constructed with total assets-based screens. The turnover analysis revealed that SCEPs are relatively costly in practice. Originality/value This study investigates the performance of Sharīʿah-compliant portfolios in the context of seven different screening guidelines. The effects of transaction cost and performance attribution to different risk factors represent the key contributions of this study.
Keywords: 330; Performance evaluation; Portfolio construction; Screening guidelines; Sharīʿah-compliant equity portfolios; Sharīʿah investment principles